Epoxidation of (E,E)-Cinnamylideneacetophenones Using Salen Mn(III) as Catalyst - Santos, Clementina M.M. (2011)
Salen Mn(III) complexes are efficient and practical catalysts for the epoxidation of various α,β-unsaturated carbonyl compounds. Among common oxidants used are iodosylbenzene, sodium hipochlorite, oxone, peracids and dimethyldioxirane [1]. Although the epoxidation of cinnamylideneacetophenones have already been reported in literature (by Julia’s epoxidation using hydrogen peroxide as oxidant [2] and by oxidation with dimethyldioxirane [3]), no studies were performed using these kind of salen Mn(III) complexes as catalysts. On these basis, we developed a study on the epoxidation of cinnamylideneacetophenones 1, catalyzed by commercially available Jacobsen’s catalyst [salen Mn(III)] and using iodosylbenzene and hydrogen peroxide as oxidants. Several experimental conditions have been used and the γ,δ-monoepoxides 2 and, in same cases, the diasteriomeric mixture of α,β:γ,δ-diepoxides 3 have been obtained. In this communication, we report the synthetic details and structural characterisation of the mono 2 and diepoxides 3 obtained.